The preference of prose when Al-Kala’i - Latli, Sami (Journal of Human Sciences, 2023)
This article deals with the superiority of prose in Ibn Abd al-Ghafoor al-Kala’i through his book ( ihkam sanaat al kalam ) "The Correctness of the Workmanship of Speech". Al-Kala’i used a method of inference which is the method of inference. On the contrary, he followed the disadvantages and miseries of poetry to conclude that prose is better than it is not available, And poetry - in his view - called for bad literature, and preaches lies and the disadvantages of morality, and victory for vanity, in addition to being available to the weight that is necessary to sing and sing, and singing leads to immorality. As for prose, he avoids all this, which calls for the abandoned, or clings to the impenetrable.